Normal Burr Cell Value Range in Healthy Adults - Danny Ernest Jonas Luhulima; Erida Manalu; Eric Meijer; Ria Amelia (GLOBAL HEALTH SCIENCE GROUP, 2025)
Burr cells or also known as echinocytes are erythrocytes with short spicules evenly spaced and appear pale in the middle. Burr cells are found in patients with chronic kidney disease, burns, liver disease, uremia, microangiopathic hemolytic anemia, pyruvate kinase deficiency, post-transfusion, or can be found in the form of artifacts. This study aims to find the range of normal burr cell values in healthy adults and to find the correlation between burr cells with urea, creatinine, cholesterol, SGPT, and gender. The method used is a quantitative descriptive research design with a cross-sectional approach. Samples were taken using a purposive sampling technique, and 54 subjects who met the inclusion and exclusion criteria were analyzed for patient characteristics and laboratory results. The results showed a very weak relationship between burr cells with gender, creatinine, and SGPT with a correlation value of <0.1 and a weak relationship between burr cells with urea and cholesterol with a correlation value of >0.1 - <0.3. The normal burr cell value range was obtained with a lower limit value of 0 and an upper limit value of 30.88 burr cells per 1000 erythrocytes.